The art of professing in Bourbon Mexico : crowned-nun portraits and reform in the convent - Cordova, James M., 1974- (University of Texas Press, 2014)
"Offering a pioneering interpretation of the "crowned nun" portrait, this book explores how visual culture contributed to local identity formation in Mexico"--